Albumin versus balanced crystalloid for resuscitation in the treatment of sepsis: A protocol for a randomised controlled feasibility study, "ABC-Sepsis". (February 2023) - Cafferkey, John; Ferguson, Andrew; Grahamslaw, Julia; Oatey, Katherine; Norrie, John; Lone, Nazir; Walsh, Timothy; Horner, Daniel; Appelboam, Andy; Hall, Peter; Skipworth, Richard; Bell, Derek; et al.
Background: Patients presenting with suspected sepsis to secondary care often require fluid resuscitation to correct hypovolaemia and/or septic shock. Existing evidence signals, but does not demonstrate, a benefit for regimes including albumin over balanced crystalloid alone. However, interventions may be started too late, missing a critical resuscitation window. Methods: ABC Sepsis is a currently recruiting randomised controlled feasibility trial comparing 5% human albumin solution (HAS) with balanced crystalloid for fluid resuscitation in patients with suspected sepsis. This multicentre trial is recruiting adult patients within 12 hours of presentation to secondary care with suspected community acquired sepsis, with a National Early Warning Score ≥5, who require intravenous fluid resuscitation. Participants are randomised to 5% HAS or balanced crystalloid as the sole resuscitation fluid for the first 6 hours. Objectives: Primary objectives are feasibility of recruitment to the study and 30-day mortality between groups. Secondary objectives include in-hospital and 90-day mortality, adherence to trial protocol, quality of life measurement and secondary care costs. Discussion: This trial aims to determine the feasibility of conducting a trial to address the current uncertainty around optimal fluid resuscitation of patients with suspected sepsis. Understanding the feasibility of delivering a definitive study will be dependent on how the study team are able to negotiate clinician choice, Emergency Department pressures and participant acceptability, as well as whether any clinical signal of benefit is detected.